All conducting polymer electrodes for asymmetric solid-state supercapacitors1. Issue 14 (14th April 2015) - Kurra, Narendra; Wang, Ruiqi; Alshareef, H. N.
<x xml:space="preserve">Abstract</x> Solid state asymmetric supercapacitors are fabricated by employing conducting polymers, such as polyaniline and poly(3, 4-ethylenedioxythiophene) as positive and negative electrodes, respectively.